A conceptual model of performance and satisfaction for main participants of construction project coalition - Robby Soetanto; David G. Proverbs; Patricia Cooper (1999)
The UK construction industry has long been criticized for engendering adversarial relationships among project participants. The nature of interrelationships ultimately determines overall project performance, in terms of finished product, and levels of performance and satisfaction for the participants. To investigate these interrelationships, the performance and satisfaction of each individual participant must be considered. Better understanding of the interrelationships should help reduce adversarialism and improve the performance and satisfaction of each participant. The possible interrelationships that may exist are discussed based on ‘soft knowledge’ approaches, i.e. psychology, organizational behaviour and sociology. The paper presents a conceptual model of performance and satisfaction for main participants of the project coalition. The ultimate aim of the research is described, that is development of a predictive model for optimizing the interrelationships. The model will determine participant performance levels that would acquire high levels of satisfaction for each participant. This prediction is based on participant performance attributes (i.e. characteristics of that organization, such as past experience, turnover, references, etc.) and interrelationships. This should provide a basis for participant self-evaluation and problem anticipation, ultimately leading to enhancement of overall project performance.